Man of the world the further endeavors of Bill Clinton - Conason, Joe (Simon & Schuster, 2016)
A veteran political journalist chronicles the post-presidential achievements and adventures of Bill Clinton, drawing on interviews with dozens of the former President's colleagues, friends, supporters and family members to examine his philanthropic work, the charges of corruption levied against him, and the ways he continues to inspire and infuriate the world.